Racing an opponent: Alteration of pacing, performance, and muscle-force decline but not rating of perceived exertion - Konings, M. J.; Parkinson, J.; Zijdewind, I.; Hettinga, F. J. (International Journal of Sports Physiology and Performance, 2018)
Purpose: Performing against a virtual opponent has been shown to invite a change in pacing and improve time-trial (TT) performance. This study explored how this performance improvement is established by assessing changes in pacing, neuromuscular function, and perceived exertion. Methods: After a peak-power-output test and a familiarization TT, 12 trained cyclists completed two 4-km TTs in randomized order on a Velotron cycle ergometer. TT conditions were riding alone (NO) and riding against a virtual opponent (OP). Knee-extensor performance was quantified before and directly after the TT using maximal voluntary contraction force (MVC), voluntary activation (VA), and potentiated doublet-twitch force (PT). Differences between the experimental conditions were examined using repeated-measures ANOVAs. Linear-regression analyses were conducted to associate changes in pacing to changes in MVC, VA, and PT. Results: OP was completed faster than NO (mean power output OP 289.6±56.1 vs NO 272.2±61.6 W; P=.020), mainly due to a faster initial pace. This was accompanied by a greater decline in MVC (MVC pre vs post -17.5%±12.4% vs -11.4%±10.9%, P=.032) and PT (PT pre vs post -23.1%±14.0% vs -16.2%±11.4%, P=.041) after OP than after NO. No difference between conditions was found for VA (VA pre vs post -4.9%±6.7% vs -3.4%±5.0%, P=.274). Rating of perceived exertion did not differ between OP and NO. Conclusion: The improved performance when racing against a virtual opponent was associated with a greater decline in voluntary and evoked muscle force than riding alone, without a change in perceived exertion, highlighting the importance of human-environment interactions in addition to one`s internal state for pacing regulation and performance.